Pengembangan Domain Specific Language untuk Aplikasi CRUD Berbasis Web - Michael Adrian Halomoan; Agi Putra Kharisma; Marji Marji (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Domain Specific Language (DSL) is a programming language designed to solve specific problems from a domain and has a limited syntax. This DSL can be useful for speeding up a job arrangement. By using DSL, we can determine the basic system functionality and automatically generate a source code. In the development process of web applications, especially in terms of implementation, developers are required to be able to produce a web application that is fast, and also according to the needs desired by the user or users who want to use the web. The problem that arises from the development process is that there are differences in requirements or requests, so that there is a gap between the program code and the concept, which includes modeling, generators, and the output of the system. To speed up the manufacturing process, a Domain Specific Language Development was carried out to be able to create a website with a predetermined domain, so that the development process could start more quickly. Based on these problems, a website application was developed by doing a domain analysis, using DSL, Xtext library, and the PHP programming language. This study produces a simple CRUD application to store student data which is the result of the implementation of the Domain Specific Language design. From the tests that have been carried out, the value is 100% valid on unit testing, and validation which shows that the system functions are in accordance with the design.